A comparative study on the fluoride level in breast milk from mothers in Bacoor, Cavite and Manila - Caones, Dorothy Jennifer; Sobrevinas, Rachelle U.; Santos, Jessica R. (Adviser).
Water fluoridation has not yet been advocated throughout the country. The fluoride level of water in Cavite is 2.0 ppm while it is 0.1 ppm in Manila. The objective of the study is to determine whether the difference in fluoride level of water in Manila and Bacoor can be reflected on the amount of fluoride in breast milk of mothers living in the two areas. 30 mothers from Cavite and 20 from Manila were asked to extract 20 ml. of their breast milk and place them in a test tube. The samples were analyzed for F concentration at U.P. Diliman using the Fluoride ion Selective Electrode Method. The derived result is tc = 12.46 ug/1 (Mean in Cavite is 12.22 ug/1; Manila. 6.92 tig/1) which is greater than 1.96 obtained in the t-distribution table at 5% level of significance. This shows that F level of breast milk in Cavite is higher than in Manila. Therefore, the F level in breast milk is affected by water fluoride content.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.